Reversal of warfarin anticoagulation in geriatric traumatic brain injury due to ground-level falls - Paisley, Michael John (Trauma Surg Acute Care Open, 2019)
BACKGROUND: The efficacy of prothrombin complex concentrate (PCC) compared with fresh frozen plasma (FFP) for reversal of oral anticoagulants has not been investigated in geriatric patients suffering intracranial hemorrhage (ICH) due to a ground-level fall (GLF). METHODS: Patients 65 years and older who were treated at Santa Barbara Cottage Hospital between January 2011 and March 2018 with ICH after a GLF while taking warfarin were reviewed. Patients were reversed with either FFP (n=25) or PCC (n=27) and patient outcomes were compared. Separate analyses were conducted for patients who received adjuvant vitamin K administration and those who did not. RESULTS: Mortality rates, hospital length of stay, intensive care unit admission and length of stay were similar for both FFP and PCC intervention. There was no difference in radiological progression of hemorrhage within the first 24 hours of admission (FFP: 36%, PCC: 43%, p=0.365). In patients who had international normalized ratio (INR) values measured prior to intervention, 81% (17 out of 21) of the PCC group reached an INR value below 1.5 within an 8-hour period, whereas only 29% (4 out of 14) of the FFP group did (p=0.002). Vitamin K was concomitantly given to 28% of the patients receiving FFP, and 81% of those patients receiving PCC. No significant differences in outcomes were found whether adjunctive vitamin K was administered or not, in either FFP or PCC group. However, when vitamin K was not administered, the PCC group had a higher rate of INR reversal (80% vs. 10% for FFP, p=0.006). CONCLUSION: Administration of PCC is as effective in short-term outcomes as FFP in treating geriatric patients on warfarin sustaining an ICH after a GLF. INR reversal was more successful, significantly faster, and required lower infusion volumes in patients receiving PCC. LEVEL OF EVIDENCE: Level III.